Exoskeleton Arm : the first step of real life iron suit - Rahman, Md. Sadiur; Avi, Md. Tanjil Rashid (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.